Returns to language skills in transition economies - Astghik Mavisakalyan (IZA World of Labor, 2017)
In many transition countries, the collapse of communism ushered in language reforms to adapt to the newfound independence from the Soviet Union and openness to the rest of the world. Such reforms may have implications for individuals' economic opportunities, since foreign language proficiency may enhance or signal productivity in the labor market. Recent empirical evidence documents positive labor market returns to English language skills in transition countries. However, Russian language proficiency also remains economically valuable, and nationalist language policies may lead to future loss of economic opportunities.
Keywords: J21; J24; P23; 330; language; human capital; labor markets; transition economies